Analisis Lapisan Serat Kulit Jagung Kering Dengan Pengaruh NaOH 4% Komposit Matriks Polyester Terhadap Pengujian Tarik dan Bending: Bahasa Indonesia - Yus Andi, Zulfan; Yuliyanto, Yuliyanto; Razqi, Fadilla Muhamad (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to analyze the effect of dry corn husk fiber layers with a 50% volume fraction on the mechanical properties of composites made using the hand lay-up method and alkali NaOH treatment. The corn husk fibers were treated with 4% NaOH for 1, 2, and 3 hours at temperatures of 80°C, 90°C, and 100°C to produce composites with polyester resin. Tensile and bending tests were conducted according to ASTM D-638 and ASTM D-790 standards. The results showed that NaOH treatment for 3 hours at 90°C produced the highest tensile strength of 21.1 Mpa, while NaOH treatment for 1 hour at 80°C produced the highest bending strength of 53.0 Mpa. On the other hand, NaOH treatment for 2 hours at 80°C resulted in the lowest tensile strength of 5.84 Mpa, and NaOH treatment for 2 hours at 100°C resulted in the lowest bending strength of 8.53 Mpa. Longer treatment durations and higher temperatures effectively remove lignin and hemicellulose, increasing tensile strength but can damage the fiber structure for bending tests. This study demonstrates the potential of corn husk fibers as an environmentally friendly and sustainable composite material.